2010
DOI: 10.1152/ajpcell.00511.2009
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular acidosis activates ASIC-like channels in freshly isolated cerebral artery smooth muscle cells

Abstract: Recent studies suggest that certain acid-sensing ion channels (ASIC) are expressed in vascular smooth muscle cells (VSMCs) and are required for VSMC functions. However, electrophysiological evidence of ASIC channels in VSMCs is lacking. The purpose of this study was to test the hypothesis that isolated cerebral artery VSMCs express ASIC-like channels. To address this hypothesis, we used RT-PCR, Western blotting, immunolabeling, and conventional whole cell patch-clamp technique. We found extracellular H+-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…Prolonged acidification affects vascular smooth muscles and contributes to baseline blood pressure and vascular disease (74). In rodents, ASIC1b is expressed in these cells and may mediate a depolarizing response to acidosis (73). We did observe some hVariant 3 expression in non-neuronal tissues (supplementary data and Fig.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Prolonged acidification affects vascular smooth muscles and contributes to baseline blood pressure and vascular disease (74). In rodents, ASIC1b is expressed in these cells and may mediate a depolarizing response to acidosis (73). We did observe some hVariant 3 expression in non-neuronal tissues (supplementary data and Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, ASIC1b has been implicated in vascular smooth muscle cell physiology (73). Prolonged acidification affects vascular smooth muscles and contributes to baseline blood pressure and vascular disease (74).…”
Section: Discussionmentioning
confidence: 99%
“…Whole cell currents were recorded using conventional patch-clamp techniques with an Axopatch 200B amplifier (Axon Instruments) interfaced to a PC through Digidata1440A digitizer (Axon Instruments) as previously described (4,5). Data were sampled at 5 kHz and filtered at 1 kHz using a low-pass Bessel filter.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we showed ASIC-like channels in cerebral VSMCs tend to be electrically silent although the underlying reason is unclear [10]. Recent reports suggest ASIC currents are modulated by oxidationreduction; reducing agents potentiate and oxidizing agents inhibit certain ASIC currents [11][12][13].…”
Section: Introductionmentioning
confidence: 90%
“…Cerebral arteries were dissected from the brain and collected into an ice-cold cell isolation solution containing (in mM) 140 NaCl, 5 KCl, 0.15 CaCl 2 , 1 MgCl 2 , 10 HEPES, and 5.5 D-glucose, pH 7.4. To isolate VSMCs appropriate for evaluating the effect of reducing agents, we modified our previous cell isolation method by replacing papain, which requires the reducing agent DTT for activation, with protease Type XIV [10]. Briefly, cells were first incubated with 1 mg/ml Protease Type XIV (Sigma-Aldrich, St. Louis, MO) and 2 mg/ml Collagenase Type IV (Worthington) for 5 min, followed by 2 mg/ml Collagenase Type IV for 5 min at room temperature.…”
Section: Preparation Of Vsmcsmentioning
confidence: 99%